Some reflections on journalism education and journalism culture - Balčytienė, Auksė; Lauk, Epp (Žurnalistikos tyrimai, 2009)
A consequence of globalization of media economy and technology for journalism lies in the unification of the production processes of media content. Differences between journalistic production routines and applied principles are diminishing towards more popularized, more commercialized production of content (Hallin & Mancini, 2004). Furthermore, journalists in many countries around the world work in basically similar professional environments; they use similar equipment and technology and share a common occupational ideology. Michael Schudson (2001:153) describes the occupational ideology of journalism as cultural knowledge that constitutes ‘news judgment’, rooted deeply in the communicators’ consciousness. This ‘cultural knowledge’ comprises certain characteristics and values, which journalists generally agree upon as a basis of journalistic practice, and function ‘to self-legitimize their position in society’ (Deuze, 2005: 446).